Towards the successful implementation of the updated OECD Guidelines for Multinational Enterprises - Tadahiro Asami (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2012)
Manfred Schekulin and John Evans have each written Perspectives discussing the 2011 update to the OECD's Guidelines for Multinational Enterprises. The Guidelines have several potential impacts, including impacts on MNEs' interactions with their supply chains. Further, to be successful, it is important that the Guidelines are incorporated into MNEs' codes of conduct. It is also essential for emerging markets to adhere to the Guidelines.
Keywords: 330